Induction of Viable but Non-Culturable State in Clinically Relevant Staphylococci and Their Detection with Bacteriophage K - Katja Šuster; Andrej Cör (MDPI AG, 2023)
Prosthetic joint infections are frequently associated with biofilm formation and the presence of viable but non-culturable (VBNC) bacteria. Conventional sample culturing remains the gold standard for microbiological diagnosis. However, VBNC bacteria lack the ability to grow on routine culture medium, leading to culture-negative results. Bacteriophages are viruses that specifically recognize and infect bacteria. In this study, we wanted to determine if bacteriophages could be used to detect VBNC bacteria. Four staphylococcal strains were cultured for biofilm formation and transferred to low-nutrient media with different gentamycin concentrations for VBNC state induction. VBNC bacteria were confirmed with the BacLightTM viability kit staining. Suspensions of live, dead, and VBNC bacteria were incubated with bacteriophage K and assessed in a qPCR for their detection. The VBNC state was successfully induced 8 to 19 days after incubation under stressful conditions. In total, 6.1 to 23.9% of bacteria were confirmed alive while not growing on conventional culturing media. During the qPCR assay, live bacterial suspensions showed a substantial increase in phage DNA. No detection was observed in dead bacteria or phage non-susceptible E. coli suspensions. However, a reduction in phage DNA in VBNC bacterial suspensions was observed, which confirmed the detection was successful based on the adsorption of phages.